2022
DOI: 10.2196/41356
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Satisfaction With Telehealth Services During The COVID-19 Pandemic: Cross-sectional Survey Study

Abstract: Background Since March 2020, the need to reduce patients’ exposure to COVID-19 has resulted in a large-scale pivot to telehealth service delivery. Although studies report that pregnant women have been generally satisfied with their prenatal telehealth experiences during the pandemic, less is known about telehealth satisfaction among postpartum women. Objective This study examined telehealth satisfaction among both pregnant and recently pregnant women du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…Yang penting, tampaknya peningkatan kecemasan bisa diatasi, dilaporkan bahwa perempuan yang awalnya skeptis terhadap telehealth umumnya merasa ketakutannya berkurang setelah menggunakan model layanan ini (Konnyu et al, 2023). Demikian pula, diidentifikasi melalui 25 wawancara semi-terstruktur bahwa perempuan memiliki kekhawatiran mengenai pemantauan mandiri dan aksesibilitas telehealth, namun hal ini dapat diatasi dengan menghadiri janji temu dengan penyedia layanan yang sudah mereka kenal, dan menyoroti pentingnya kesinambungan layanan (Nguyen et al, 2022).…”
Section: Stres Dan Kecemasan DI Kalangan Pengguna Telemedisunclassified
See 2 more Smart Citations
“…Yang penting, tampaknya peningkatan kecemasan bisa diatasi, dilaporkan bahwa perempuan yang awalnya skeptis terhadap telehealth umumnya merasa ketakutannya berkurang setelah menggunakan model layanan ini (Konnyu et al, 2023). Demikian pula, diidentifikasi melalui 25 wawancara semi-terstruktur bahwa perempuan memiliki kekhawatiran mengenai pemantauan mandiri dan aksesibilitas telehealth, namun hal ini dapat diatasi dengan menghadiri janji temu dengan penyedia layanan yang sudah mereka kenal, dan menyoroti pentingnya kesinambungan layanan (Nguyen et al, 2022).…”
Section: Stres Dan Kecemasan DI Kalangan Pengguna Telemedisunclassified
“…Begitu pula pada uji kelayakan BuMP tahun 2017, ditemukan bahwa pemantauan tekanan darah jarak jauh mengurangi kecemasan wanita terhadap kesehatan, terutama jika mereka memiliki pengalaman hipertensi atau preeklampsia sebelumnya (Hinton et al, 2017). Dalam studi crosssectional terhadap 403 wanita, mencatat bahwa pendidikan dan pendapatan berhubungan positif dengan kepuasan telehealth, yang menunjukkan perlunya mendukung perempuan dari latar belakang yang kurang beruntung ketika mengakses layanan ini (Mittone et al, 2022).…”
Section: Stres Dan Kecemasan DI Kalangan Pengguna Telemedisunclassified
See 1 more Smart Citation
“…Similarly, in the 2017 BuMP feasibility trial, Hinton et al [ 87 ] found that remote blood pressure monitoring reduced women’s health anxiety, particularly if they had previous experiences of hypertension or preeclampsia. In a cross-sectional study of 403 women, Mittone et al [ 88 ] noted that education and income were positively associated with telehealth satisfaction, demonstrating the need to support women of disadvantaged backgrounds when accessing these services.…”
Section: Consumer Satisfactionmentioning
confidence: 99%